Effect of increasing temperatures on duckweed growth, photosynthetic performance and frond ontogenesis - Muhammad Irfan; Muhammad Adil Chaudhry; Manuela Bog; Sándor Szabó; Ilona Mészáros; Marcel A. K. Jansen; Viktor Oláh (Plant Cell Reports, 2026)
Key message Duckweeds offer a suitable platform to study the effects of elevated temperatures on aquatic plants, and chlorophyll fluorescence imaging can reveal frond-level distribution of temperature stress. Abstract Temperature rise associated with climate change poses a major challenge for aquatic plants. It has a strong influence on their physiological performance and, consequently, their competitive ability and fitness. Yet comparative studies of impacts on different species remain scarce. This study investigated the effects of four different temperature regimes between 20 and 35 °C on five duckweed species ( Spirodela polyrhiza , Landoltia punctata , Lemna gibba , Lemna minor and Lemna minuta ) by integrating growth- and photosynthesis-based parameters. We also recorded spatial patterns of photosystem II efficiency within fronds using chlorophyll a fluorescence imaging to understand how temperature stress is distributed throughout the frond development. The results highlighted substantial inter-specific variation in thermal responses and underscore the importance of integrating physiological and growth-based indicators to predict aquatic plants’ responses to climatic warming. Through simultaneous measurement of growth performance, photosynthetic efficiency and within-frond heterogeneity, this study provides mechanistic insights into how rising temperatures may influence duckweeds. Such knowledge is essential for predicting future shifts in freshwater primary productivity, species dominance, biological invasions and ecosystem stability under the current global warming scenario.